Interindividual and interoccasion variability of toxicokinetic parameters of uptake, exhalation, and metabolism of ethylene - Florian A. Schirm; Silvia Selinski (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2000)
A basic part in the risk assessment of potential carcinogens is the determination of toxicokinetic parameters. The partition of the xenobiotic in the body of experimental animals is a first step of the biochemical pathway of the formation of DNA adducts which might lead to the development of cancer. The aim of extrapolation of toxicological data from experimental animals to the human organism requires a valid characterisation of the considered processes for the whole species, i. e. population parameters, moreover accounting for the variability within and between individuals. This paper presents the results of an inhalation study with one of the basic petrochemical industrial compounds, ethylene (ethene). Two nonlinear four-stage hierarchical models for a repeated measurement design which are of different complexity are presented. The estimation of the individual and population parameters as well as of the covariance matrices is performed by an EM algorithm.
Keywords: 519; ethylene; ethylene oxide; risk assessment; toxicokinetics; population parameters; two-compartment model; nonlinear hierarchical model; Bayes estimates; EM algorithm; repeated measurement